Learning Development Extensive Online Based Reading in English Students UNTIRTA FKIP - Juniardi, Yudi; Pahamzah, John; Sampurna, Pupun (Opción, 2019)
The use of information technology in teaching English as a foreign language is essential and useful as a medium of teaching and learning. Yunus, et.al (2013) states that there are several benefits to using ICT; attracting students ‘ atten- tion, facilitating student learning, helping to improve students ‘ vocabulary knowledge and promoting meaningful learning. Related to it will be conduct- ed research development of an extensive reading learning online/web based in the English Department of Sultan Ageng Tirtayasa University. This develop- ment study was conducted to see the effectiveness of online-based learning in learning extensive reading (ER) to collect data, researchers use literature re- view, reading comprehension tests, observations and interviews. Learning Ex- tensive-based Reading online is implemented in learning Extensive reading. Researchers develop online learning by using WordPress as a program used to create learning websites Extensive reading. In the web it is filled with learning content, learning materials, discussion forums, and evaluation. Students are given some text via on line and they are asked to answer a test reading under- standing online. The results of this study show the following: (1) Learning to read by using WordPress as a learning medium can be one of the alternative and effective media; (2) WordPress is an online-based application that can be create for learning activities by designing it as a web of learning; (3) Word Press can be used as one of the alternative media in learning Extensive Read- ing Online (ERO); (4) ERO is effectively used in the extensive of Reading; and lastly (5) ERO motivates students in extensive reading learning.